2011
DOI: 10.1080/10665684.2011.563182
|View full text |Cite
|
Sign up to set email alerts
|

The Right Time and Place? Middle School Language Arts Teachers Talk about Not Talking about Sexual Orientation

Abstract: In this article we report results of a qualitative interview study focusing on middle school Language Arts teachers' perceptions, attitudes, and reported practices related to LGBQ topics. The study found that virtually all of the teacher participants recognized that the topic of same-sex sexuality was important for their students, yet the teachers used a variety of strategies to avoid or redirect discussion of the topic. We argue that teacher responses indicate that they generally reinforced the heteronormativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…Of paramount concern is that these pre-service teachers were either unfamiliar with or in complete denial of the concept of heteronormativity and the historical role of schools in enforcing compulsory heterosexuality. While the findings presented here are from just one university, the results echo the few other similar studies done (Haertling-Thein, 2013;Puchner & Klein, 2011), strongly arguing that there remains a great deal of resistance to incorporating LGBTQ topics and texts in English language arts classes.…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…Of paramount concern is that these pre-service teachers were either unfamiliar with or in complete denial of the concept of heteronormativity and the historical role of schools in enforcing compulsory heterosexuality. While the findings presented here are from just one university, the results echo the few other similar studies done (Haertling-Thein, 2013;Puchner & Klein, 2011), strongly arguing that there remains a great deal of resistance to incorporating LGBTQ topics and texts in English language arts classes.…”
Section: Discussionsupporting
confidence: 41%
“…Unfortunately, researchers have found mixed results when examining pre-service teachers' willingness to confront homophobia in the classroom (Bellini, 2012;Mudrey & Medina-Adams, 2006;Robinson & Ferfolja, 2001;Schmidt, Chang, Carolan-Silva, Lockhart, & Anagnostopoulos, 2012). In one study, Puchner and Klein (2011) interviewed 15 middle school teachers on the topic of sexual orientation and found that most of the teachers avoided LGBTQ topics in the classroom, that some actively repeated homophobic messages and others even "blocked student attempts to disrupt the dominant discourse" (p. 236). While three teachers were described having anti-homophobic stances, they were mostly passive due to fears of retribution from their communities.…”
mentioning
confidence: 99%
“…A number of curriculum scholars have highlighted the inclusion of topics related to sexuality and gender remains rare and, when present, the information is often missing important contextualization and is therefore taught in incorrect, unbalanced, and harmful ways (Macgillivray, 2000;Meyer, 2009). In discussions pertaining to sexual health, homosexuality often still remains taboo (Zimmerman, 2015), and when it is covered, is generally related to risktaking behaviours and in the context of AIDS or as a pathology, thus maintaining damaging stereotypes (Friend, 1993;MacGillivray, 2000;Meyer, 2009;Puchner & Klein, 2011). The result is that many students are either uneducated or mis-educated on topics related to gender and sexual diversity, which impacts not only gender and sexual minority youth, but all students in their developing identity and beliefs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Gender and sexual minorities experience perpetually higher rates of psychological distress, and this difference is almost exclusively the result of culturally maintained stigma, discrimination, and victimization (Callaghan, 2009(Callaghan, , 2016Crowell, Galliher, Dehlin, & Bradshaw, 2015;Meyer, 2003). Despite an awareness of the oppression experienced by sexual and gender minority students, many public school educators acknowledge they routinely avoid discussing gender and sexual diversity in their classrooms out of a fear of reprimand (Leonardi & Saenz, 2014;Puchner & Klein, 2011;Sieben & Wallowitz, 2009). When teachers avoid content inclusive of sexual diversity, heterosexuality remains privileged as the norm, further undermining the emotional and developmental needs of sexual and gender minority students (Macgillivray, 2000;Puchner & Klein, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation